Total ankle arthroplasty in under 50-year-old patients Ten years follow-up: Retrospective analysis - Núñez-Samper, Mariano; Parra, Guillermo; Duran, Eldis Lao (Tobillo y Pie, 2017)
Objective: Age below 50 years has traditionally been considered a contraindication for total ankle arthroplasty, considering excessive the use and stress it undergoes in this particular group, favouring an early implant loosening and therefore arthrodesis has been considered as “gold standard”. In this paper we report the results of a ten-year follow-up of ten under 50-year-old patients who underwent total ankle arthroplasty. Methods: Clinical, functional and radiological results have been recorded and analysed, as well as the complications arises with both implants used, Ramses II (FH orthopedics) and Star Tm (SB Inc). Results: Preoperative AOFAS score ranged from 30 to 70 points, with a mean score of 57.4, as opposed to 25 to 83 points at 10 year follow-up. Range of motion ranged between 20 to 30º at pre-operative evaluation, improving to 45-55º at follow-up, showing an improvement of 25º. Three patients (30%) reported no pain at 10 years, whilst 40% reported occasional pain, 20% moderate pain and 10% endured severe pain, with low impact on daily activities. 90% returned to normal life and 30% returned to sports (ski, tennis…) although not at the same level. The level of satisfaction was very high in 10%, moderate in 60% and low or unsatisfied in 20%, similar to other series in literature. Conclusion: At mid-term follow-up, we have found ankle replacements to produce the same results in terms of complications and outcome as in older patients’ groups. Therefore, indication criteria have to be strict and restricted to patients where solid implantation of the prosthesis can be expected. Level of evidence: IVth